Role of perception cross-cultural communication. - Herwani Ahmat. (2013)
The fundamental question that we tried to answer with this study was how differing perceptions of culture could constitute to a cross-cultural communication barrier. To start off, we compared two significantly different cultures, that of America and Singapore, where differing perceptions prevailed. We divided the study into two distinct parts. The pilot study, or Stage 1, was conducted to identify culture and other variables that gave rise to perceptual differences. Instinctively, we came up with six variables that we felt would affect perception. They were culture, the number of years worked in Singapore, the number of years of overseas education, the length of cultural training attended by the expatriate, the age of the American manager and the number of years worked overseas. Our sample population of 10 expatriates were randomly chosen from an exhaustive list of American multinational corporations based in Singapore, and their immediate subordinates, numbering 30, were also included. The data collection methods were interviews for the managers and questionnaires for the local subordinates.